Abnormal MEG oscillatory activity during visual processing in the prefrontal cortices and frontal eye-fields of the aging HIV brain. - Tony W Wilson (Public Library of Science (PLoS), 2013)
Objective Shortly after infection, HIV enters the brain and causes widespread inflammation and neuronal damage, which ultimately leads to neuropsychological impairments. Despite a large body of neuroscience and imaging studies, the pathophysiology of these HIV-associated neurocognitive disorders (HAND) remains unresolved. Previous neuroimaging studies have shown greater activation in HIV-infected patients during strenuous tasks in frontal and parietal cortices, and less activation in the primary sensory cortices during rest and sensory stimulation. Methods High-density magnetoencephalography (MEG) was utilized to evaluate the basic neurophysiology underlying attentive, visual processing in older HIV-infected adults and a matched non-infected control group. Unlike other neuroimaging methods, MEG is a direct measure of neural activity that is not tied to brain metabolism or hemodynamic responses. During MEG, participants fixated on a centrally-presented crosshair while intermittent visual stimulation appeared in their top-right visual-field quadrant. All MEG data was imaged in the time-frequency domain using beamforming. Results Uninfected controls had increased neuronal synchronization in the 6-12 Hz range within the right dorsolateral prefrontal cortex, right frontal eye-fields, and the posterior cingulate. Conversely, HIV-infected patients exhibited decreased synchrony in these same neural regions, and the magnitude of these decreases was correlated with neuropsychological performance in several cortical association regions. Conclusions MEG-based imaging holds potential as a noninvasive biomarker for HIV-related neuronal dysfunction, and may help identify patients who have or may develop HAND. Reduced synchronization of neural populations in the association cortices was strongly linked to cognitive dysfunction, and likely reflects the impact of HIV on neuronal and neuropsychological health.